2012
DOI: 10.1002/adv.21290
|View full text |Cite
|
Sign up to set email alerts
|

Natural Cellulosic Polymers as Potential Reinforcement in Composites: Physicochemical and Mechanical Studies

Abstract: Renewable cellulosic biofibers appear to be a promising substitute to synthetic fibers as reinforcement in different kinds of polymers. The prime objective of this work was to determine water absorption, chemical resistance, and mechanical properties of the green composites reinforced with ecofriendly natural cellulosic Saccharum cilliare fibers. The mechanical and physicochemical properties of the green composites have been investigated as a function of fiber loading for assessing their applicability in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Such a hydrophilic nature of natural fibers can be a drawback, which makes them less competitive compared to glass fibers. When in wet conditions natural fiber composites absorb moisture from a moist atmosphere resulting in fiber swelling or interface disbands that make the natural fiber composite limited to interior parts of the automobile . Singh and Gupta found that the strength of a sisal/polyester composite was 13–31% lower when fully immersed than at 95% RH.…”
Section: Challengesmentioning
confidence: 99%
“…Such a hydrophilic nature of natural fibers can be a drawback, which makes them less competitive compared to glass fibers. When in wet conditions natural fiber composites absorb moisture from a moist atmosphere resulting in fiber swelling or interface disbands that make the natural fiber composite limited to interior parts of the automobile . Singh and Gupta found that the strength of a sisal/polyester composite was 13–31% lower when fully immersed than at 95% RH.…”
Section: Challengesmentioning
confidence: 99%
“…The key problem in producing composite materials is to achieve good interphase adhesion between the polymer matrix and the lignocellulosic filler (Thakur et al 2013). Moreover, the unmodified lignocellulosic components show a tendency towards aggregation, which is a consequence of the intermolecular interactions (H-bonds) between the molecules of the filler.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose, consisting of 10000-25000 ˇ-(1→4)-linked glucopyranosyl repeating units has attracted the considerable attraction of research community all around the globe owing to their unique intrinsic properties such as biodegradability [1,2], easy availability [3], environmental friendliness [4,5], flexibility [6], easy processing and impressive physico-mechanical properties [7][8][9]. Using renewable materials, more eco-friendliness can be achieved relative to the conventional toxic synthetic polymer composites materials [10][11][12].…”
Section: Introductionmentioning
confidence: 99%